Синдром дисемінованого внутрішньосудинного згортання у пацієнтів, котрі перенесли гострі порушення мозкового кровообігу - Тещук, В.Й.; Тещук, В.В.; Скочко, С.П. (Актуальні проблеми транспортної медицини, 2015)
В роботі представлено аналіз лікування 17 пацієнтів з гострими порушеннями мозкового кровообігу, у котрих визначався синдром дисемінованого внутрішньосудинного згортання крові, в результаті термінальних станів, які виникли після перенесених реанімаційних втручань, та перебували на стаціонарному лікуванні в клініці нейрохірургії і неврології Військово-медичного клінічного центру Південного регіону з 2000 р. до березня 2014 р. Встановлено характерні особливості перебігу гострих порушень мозкового кровообігу, у пацієнтів з ДВЗ-синдромом. Перспективи подальших досліджень полягають у вивченні механізмів розвитку ДВЗ-синдрому при гострих порушеннях мозкового кровообігу, у зіставленні патоморфологічних особливостей з клінічними проявами інсульту та можливістю попередження вітальних порушень. Военно-медицинский клинический центр Южного региона (г. Одесса), Киевская областная клиническая больница (г. Киев) В работе представлен анализ лечения 17 пациентов с острыми нарушениями мозгового кровообращения, в которых определялся синдром диссеминированного внутрисосудистого свертывания крови, в результате терминальных состояний, которые возникли после перенесенных реанимационных вмешательств, и находились на стационарном лечении в клинике нейрохирургии и неврологии Военно-медицинского клинического центра Южного региона с 2000 гг. до марта 2014 г. Установлены характерные особенности течения острых нарушений мозгового кровообращения, у пациентов с ДВС-синдромом. Перспективы дальнейших исследований заключаются в изучении механизмов развития ДВСсиндрома при острых нарушениях мозгового кровообращения, в сопоставлении патоморфологических особенностей с клиническими проявлениями инсульта и возможностью предупреждения витальных нарушений. Providing specialized care to patients with anhionevrolohichnoyi strokes that complicated DIC has held in anhionevrolohichnyh offices, patients must arrive there as soon as possible, preferably within the “therapeutic window”. To optimize the provision of care to patients with CVA in Ukraine to create a sufficient network of specialized stroke offices equipped with CT or MRI apparatus working around the clock. In particular, it is necessary to organize regular service in the departm ent of computer tomography VMKTS PR to ensure that the KTHM all patients with CVA who admitted for hospital treatment in VMKTS PR for two hours. They should organize round the clock duty multidisciplinary teams with mandatory participation resuscitator, neurologist, neurosurgeon, cardiologist, rehabilitation. Permission to transport a patient with CVA should provide qualified anhionevroloh, which then will deal with the treatment of the patient, not the physician-organizer. or a representative of the administration. Implementation of these m easures will lead to an increase in hospitalizations for stroke patients to specialized department, reduced hospital mortality, reducing the number of patients with profound neurological disorders, increasing the number of patients with minimal consequences CVA, reducing the time patients stay in hospital.